Association between oral health and colorectal adenoma in a screening population. Issue 37 (September 2018) - Lee, Donghyoun; Jung, Kyung Uk; Kim, Hyung Ook; Kim, Hungdai; Chun, Ho-Kyung
Abstract : Abstract: Although periodontal disease and gastrointestinal tract health are closely associated, few studies have investigated whether periodontitis is a risk factor for colorectal adenoma. The aim of this study was to investigate whether there is an association between periodontitis and the risk of colorectal adenoma in asymptomatic healthy people. From January 2013 to October 2015, we retrospectively enrolled 42, 871 patients who underwent health screening at Kangbuk Samsung Hospital in South Korea. Demographic and clinical data were collected before colonoscopy. We calculated the odds ratio (OR) for adenoma in these patients. The median age was 39.3 ± 8.7 years and 70.4% of the patients were men; 32.5% had a body mass index (BMI) 25.0 kg/m 2 . The frequency of adenoma was 12% (n = 5136). A higher risk of adenoma was associated with the following factors: BMI 25.0 kg/m 2 (OR 1.51, 95% confidence interval [CI]: 1.42–1.61), current smoker (OR 1.51, 95% CI: 1.42–1.61), former smoker (OR 1.28, 95% CI: 1.19–1.37), periodontitis (OR 1.95, 95% CI: 1.82–2.0), moderate alcohol intake (OR 1.8, 95% CI: 1.69–1.93), and heavy alcohol intake (OR 2.67, 95% CI: 2.24–3.18). Being male or a former or current smoker, alcohol intake above the moderate level, and periodontitis increase the risk of colorectal adenoma. These findings suggest that controlling oral disease is important to the prevention and management of colorectal adenoma. The findings of this study could be applied to risk stratification and colorectal cancer prevention programs, including screening guidelines.